DEVELOPMENT COMMUNICATION AND YOUTH ENGAGEMENT IN SMART FISHERIES VILLAGES - Amalliah; Flora Meliana Siahaan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The limited involvement of rural youth in aquaculture management poses a significant challenge to the sustainability of fisheries human resource development within the Smart Fisheries Village (SFV) program. This study aims to examine the extent of youth engagement in aquaculture management, identify the factors influencing their participation, and formulate a development communication strategy model to support the sustainable regeneration of fisheries human resources. The study employed a descriptive qualitative approach within a constructivist paradigm. Data were collected through participant observation, in-depth interviews with SFV managers, fisheries extension officers, senior aquaculture practitioners, and rural youth, as well as document analysis. The findings indicate that youth engagement remains largely passive and is primarily concentrated at the operational level, with limited involvement in planning and decision-making processes. Low participation is influenced by interconnected psychological, structural, socio-cultural, and intergenerational communication factors. Conversely, institutional support, fisheries-based business diversification, community social capital, and women’s participation contribute positively to program sustainability. Based on these findings, the study proposes a development communication strategy model consisting of experiential communication, role-model communication, hybrid communication, collaborative communication, and inclusive communication. This model is expected to strengthen youth engagement, support fisheries workforce regeneration, and enhance the sustainability of fisheries-based rural development.